The intellectual challenges and emotional consequences of equipoise contributed to the fragility of recruitment in six randomized controlled trials() - Donovan, Jenny L. (Elsevier, 2014)
OBJECTIVE: The aim of the study was to investigate how doctors considered and experienced the concept of equipoise while recruiting patients to randomized controlled trials (RCTs). STUDY DESIGN AND SETTING: In-depth interviews with 32 doctors in six publicly funded pragmatic RCTs explored their perceptions of equipoise as they undertook RCT recruitment. The RCTs varied in size, duration, type of complex intervention, and clinical specialties. Interview data were analyzed using qualitative content and thematic analytical methods derived from grounded theory and synthesized across six RCTs. RESULTS: All six RCTs suffered from poor recruitment. Doctors wanted to gather robust evidence but experienced considerable discomfort and emotion in relation to their clinical instincts and concerns about patient eligibility and safety. Although they relied on a sense of community equipoise to justify participation, most acknowledged having “hunches” about particular treatments and patients, some of which undermined recruitment. Surgeons experienced these issues most intensely. Training and support promoted greater confidence in equipoise and improved engagement and recruitment. CONCLUSION: Recruitment to RCTs is a fragile process and difficult for doctors intellectually and emotionally. Training and support can enable most doctors to become comfortable with key RCT concepts including equipoise, uncertainty, patient eligibility, and randomization, promoting a more resilient recruitment process in partnership with patients.